Pengaruh Bimbingan Kelompok dengan Teknik Self Management untuk Meningkatkan Perilaku Hidup Bersih Santriwati - Fatimatuzzahroh; Hilda Rosida; Yogi Damai Syaputra (Journal of Sufism and Psychotherapy, 2024)
Poor cleanliness is a problem that often occurs in Islamic boarding schools. In fact, cleanliness has a big impact on the comfort and health of students. This research aims: 1) To determine the level of santriwati's clean living behavior before and after being given group guidance using self-management techniques, 2) To determine the effect of group guidance using self-management techniques to improve santriwati's clean living behavior. This research uses a quantitative method, a pre-experimental approach with a one group pretest-posttest design. The population of this study were female students in classes X and XI at the Al-Fath Cilegon Islamic Boarding School. The sample for this research consisted of 10 female students who had low hygiene behavior by taking samples using a purposive sampling technique. This research instrument uses a clean living behavior scale. Data were analyzed using descriptive analysis and Wilcoxon analysis. The results of this research are: 1) The level of santriwati's clean living behavior before being given group guidance treatment using self-management techniques is in the low category. After being given treatment, the female students' level of clean living behavior was in the high and very high categories. 2) Asymp value. Sig. (2-tailed) female students' clean living behavior before and after treatment obtained a score of 0.005 (0.005<0.05), which means Ho was rejected and Ha was accepted. These results indicate that group guidance with self-management techniques has an effect on improving female students’ clean living behavior.